2003
DOI: 10.1046/j.1523-1747.2003.12536.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of Peroxisome Proliferator-Activated Receptors and Nuclear Factor κB in Normal and Lesional Psoriatic Skin

Abstract: Abnormal epidermal proliferation and differentiation characterize the inflammatory skin disease psoriasis. Here we demonstrate that expression of PPARdelta mRNA and protein is markedly upregulated in psoriatic lesions and that lipoxygenase products accumulating in psoriatic lesions are potent activators of PPARdelta. The expression levels of NF-kappaB p50 and p65 were not significantly altered in lesional compared with nonlesional psoriatic skin. In the basal layer of normal epidermis both p50 and p65 were seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 89 publications
10
124
0
4
Order By: Relevance
“…In addition, PPARb/y-deficient mice displayed an exaggerated hyperproliferative response to TPA, suggesting that this receptor is critical for attenuating epidermal proliferation (30,52). It was suggested that in the hyperproliferative epidermis of psoriatic skin, PPARb/y overexpression mediates keratinocyte proliferation via NF-kB (44). Together, these results indicate that the absence of PPARb/y leads to increased keratinocyte proliferation and that under some experimental conditions PPARb/y activators inhibit keratinocyte proliferation.…”
Section: Effects Of Ppar and Lxr Activation On Epidermal Proliferatiomentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, PPARb/y-deficient mice displayed an exaggerated hyperproliferative response to TPA, suggesting that this receptor is critical for attenuating epidermal proliferation (30,52). It was suggested that in the hyperproliferative epidermis of psoriatic skin, PPARb/y overexpression mediates keratinocyte proliferation via NF-kB (44). Together, these results indicate that the absence of PPARb/y leads to increased keratinocyte proliferation and that under some experimental conditions PPARb/y activators inhibit keratinocyte proliferation.…”
Section: Effects Of Ppar and Lxr Activation On Epidermal Proliferatiomentioning
confidence: 91%
“…Alterations in PPAR expression in psoriasis (32,44) and the anti-inflammatory and prodifferentiating effects of PPAR and LXR activation on the epidermis described above prompted clinical trials exploring the efficacy and safety of PPAR-targeted therapy. A striking improvement of skin lesions had initially been documented in patients with psoriasis treated with the oral PPARg activator troglitazone (9,113).…”
Section: Clinical Trials In Humansmentioning
confidence: 99%
“…Several nuclear hormone liposensors, including peroxisome proliferator-activated receptor a (PPARa), PPARb/D, PPARg, and LXR-a and -b, are expressed in keratinocytes (167)(168)(169). Studies by our laboratory and others have shown that activation of PPARs and LXRs has major effects on epidermal/keratinocyte function.…”
Section: Jlr: Are Transporters For the Uptake Of Fatty Acids Present mentioning
confidence: 99%
“…Sixteen hours later the cells were lysed and samples read on a luminometer. Dose curves were plotted to determine the IC 50 for the blocking activity of the 5C9, 1B4, and 7E9 Abs.…”
Section: Cell Culture Cytokines and Other Reagentsmentioning
confidence: 99%